Bilateral Palatal Talon Cusps on Permanent Maxillary Lateral Incisors: A Case Report - Ozcelik, Bahar; Atila, Burcu (European Journal of Dentistry, 2011)
Talon cusp is a rare developmental extra cusp-like projection on the cingulum area of affected anterior teeth that may cause various functional and aesthetic problems. The present report describes a case of bilateral palatal talon cusps on permanent maxillary incisors and the treatment procedure to overcome the clinical problems associated with talon cusps. (Eur J Dent 2011;5:113-116)
Keywords: Talon cusp; Maxillary lateral incisor; Root canal therapy